2010
DOI: 10.1093/pcp/pcq108
|View full text |Cite
|
Sign up to set email alerts
|

ATHB12, an ABA-Inducible Homeodomain-Leucine Zipper (HD-Zip) Protein of Arabidopsis, Negatively Regulates the Growth of the Inflorescence Stem by Decreasing the Expression of a Gibberellin 20-Oxidase Gene

Abstract: Arabidopsis thaliana homeobox 12 (ATHB12) is rapidly induced by ABA and water stress. A T-DNA insertion mutant of ATHB12 with a reduced level of ATHB12 expression in stems had longer inflorescence stems and reduced sensitivity to ABA during germination. A high level of transcripts of gibberellin 20-oxidase 1 (GA20ox1), a key enzyme in the synthesis of gibberellins, was detected in athb12 stems, while transgenic lines overexpressing ATHB12 (A12OX) had a reduced level of GA20ox1 in stems. Consistent with these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 47 publications
2
81
0
2
Order By: Relevance
“…(Dinneny et al, 2008). Analysis of other salt-responsive genes identified several that were also strongly dependent upon ABA signaling in the endodermis, including HOMEOBOX12 (HB12), an ABA-induced gene necessary for growth suppression during water stress ( Figure 5E) (Olsson et al, 2004;Son et al, 2010). These data show that ABA signaling is enriched in the region of the root-containing LRs and that endodermal ABA signaling is necessary for many of these responses.…”
Section: Sustained Aba Signaling Is Associated With Lr Quiescence Durmentioning
confidence: 83%
“…(Dinneny et al, 2008). Analysis of other salt-responsive genes identified several that were also strongly dependent upon ABA signaling in the endodermis, including HOMEOBOX12 (HB12), an ABA-induced gene necessary for growth suppression during water stress ( Figure 5E) (Olsson et al, 2004;Son et al, 2010). These data show that ABA signaling is enriched in the region of the root-containing LRs and that endodermal ABA signaling is necessary for many of these responses.…”
Section: Sustained Aba Signaling Is Associated With Lr Quiescence Durmentioning
confidence: 83%
“…ATHB7 and ATHB12 are positive regulators of ABA inhibition of root and stem growth (Olsson et al, 2004). Recently, it has been demonstrated that ATHB12 inhibits stem growth by reducing GA20 oxidase (Son et al, 2010). Overexpression of another HD-Zip protein, ATHB5, enances ABA sensitivity during the germination and postgermination root growth stage, although its knockout plants do not exhibit any phenotypes (Johannesson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the HD-Zip I subfamily is composed of 17 members, and many of them are known to modulate plant growth in response to developmental and environmental cues (Harris et al, 2011;Henriksson et al, 2005). For instance, ATHB7, ATHB12, and ATHB13 affect plant growth under abiotic stress conditions (Olsson et al, 2004;Son et al, 2010). ATHB6, ATHB5, and ATHB20 are regulators of a subset of ABA response (Barrero et al, 2010;Himmelbach et al, 2002;Johannesson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis HD-Zip I proteins consist of 17 members: AtHB1/HAT5, AtHB3/HAt7, AtHB5-7, AtHB12, AtHB13, AtHB16, AtHB20-23, AtHB40, AtHB51-54 (Ariel et al 2010;Hu et al 2012); Arabidopsis HD-ZIP II proteins consist of nine members: AtHB2/HAT4, AtHB4, HAT1-HAT3, HAT9, HAT14, HAT17, and HAT22 (Ariel et al 2010;Hu et al 2012). In summary, members of HDZip subfamilies I and II act as the integrators of development and environmental cues and endogenous hormone signal pathway to regulate targeted gene expression and plant adaptation response (Son et al 2010;Wang et al 2013c). For example, the expression of HD-Zip I and II genes was induced by the following three environmental cues: drought/salt/ABA/cold (Harris et al 2011), light stimulation (Ariel et al 2010;Harris et al 2011), and biotic stress such as Pseudomonas syringae (Dezar et al 2011).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%